Cover Image, Volume 53, Number 11, November 2018. Issue 11 (23rd October 2018) - Sanders, Catherine D.; Leigh, Margaret W.; Chao, Kay C.; Weck, Karen E.; King, Ian; Wolf, Whitney E.; Campbell, Dennis J.; Knowles, Michael R.; Zariwala, Maimoona A.; Shapiro, Adam J.
Abstract : The cover image is based on the Original Article The prevalence of the defining features of primary ciliary dyskinesia within a cri du chat syndrome cohort, by Catherine D. Sanders MD et al., DOI:10.1002/ppul.24159 .